2019
DOI: 10.1002/jcp.28138
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and gout are associated with cancer incidence and mortality: A meta‐analysis based on cohort studies

Abstract: The association between hyperuricemia or gout and cancer risk has been investigated in various published studies, but their results are conflicting. We conducted a meta‐analysis to investigate whether hyperuricemia or gout was associated with the cancer incidence and mortality. Linear and nonlinear trend analyses were conducted to explore the dose–response association between them. The pooled relative risk (RR) and 95% confidence interval (CI) were used to evaluate cancer risk. A total of 24 articles (33 indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 54 publications
(62 reference statements)
0
33
0
Order By: Relevance
“…Also, that study only had 15 cancer‐related deaths, which limited their precision . A recent meta‐analysis evaluated the relationship between gout and cancer incidence only, not cancer mortality; thus, the data from that meta‐analysis are not directly comparable to our results .…”
Section: Discussionmentioning
confidence: 68%
“…Also, that study only had 15 cancer‐related deaths, which limited their precision . A recent meta‐analysis evaluated the relationship between gout and cancer incidence only, not cancer mortality; thus, the data from that meta‐analysis are not directly comparable to our results .…”
Section: Discussionmentioning
confidence: 68%
“…Traditional recognition of HUA was limited to its triggering of gout and related disability-adjusted of life years [1]. Recently, more studies have proved that HUA was also associated with cardiovascular diseases, renal dysfunction, and cancers [2][3][4]. For each increase of 1 mg/dL in serum uric acid (SUA) level, the pooled relative risk of stroke and coronary heart disease mortality was 1.10 and 1.13, respectively [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hyperuricemia has also been shown to be significantly associated with lifestyle-related chronic diseases, such as hypertension, diabetes [7], non-alcoholic fatty liver disease (NAFLD) [8], and cancer. In addition, a meta-analysis based on cohort studies also confirmed that hyperuricemia was associated with high cancer incidence and mortality [9].…”
Section: Introductionmentioning
confidence: 79%